2009
DOI: 10.1007/s11071-009-9519-7
|View full text |Cite
|
Sign up to set email alerts
|

A new technique to generate independent periodic attractors in the state space of nonlinear dynamic systems

Abstract: This paper proposes a method to generate several independent periodic attractors, in continuoustime nonchaotic systems (with an equilibrium point or a limit cycle), based on a switching piecewise-constant controller. We demonstrate here that the state space equidistant repartition of these attractors is on a precise zone of a precise curve that depends on the parameters of the system. We determine the state space domains where the attractors are generated from different initial conditions. A mathematical formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The first one is the generation of several independent periodic attractors. Recently, [21] demonstrated that the equidistant repartition of these attractors is in a precise zone (a controllable state space area) of a precise curve, which depends of the sine anticontrol feedback v c (t) frequency. Then, the state space domains where the attractors are generated from different initial conditions were determined.…”
Section: Anticontrol Of Chaosmentioning
confidence: 99%
See 2 more Smart Citations
“…The first one is the generation of several independent periodic attractors. Recently, [21] demonstrated that the equidistant repartition of these attractors is in a precise zone (a controllable state space area) of a precise curve, which depends of the sine anticontrol feedback v c (t) frequency. Then, the state space domains where the attractors are generated from different initial conditions were determined.…”
Section: Anticontrol Of Chaosmentioning
confidence: 99%
“…Then, the state space domains where the attractors are generated from different initial conditions were determined. Also, a mathematical formula giving the maximal attractors number in function of the controller piecewise-constant values has been deduced [21]. In this paper, we are interested by the second property: the size of the attractors.…”
Section: Anticontrol Of Chaosmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the strong non-linear modeling of switching converters [9], these converters can exhibit complex dynamical behaviors such as bifurcation and chaos with variation of a bifurcation parameter [10]. This bifurcation parameter can be the load [11], the reference voltage [12], the reference current [13,14], the inductance [15] of the converter, or a control parameter [16,17]. There is a bifurcation route towards chaos when increasing or decreasing these parameters, forcing the MOSFET to operate under harsh conditions.…”
Section: Introductionmentioning
confidence: 99%
“…After the study of the harmonics of chaotic systems [16,18], we generated attractors using a switching piecewisebinary controller in a precise but uncontrollable area of the state space [15] [17]. In this paper, we propose a switching piecewise-constant controller in continuous-time systems to generate several independent 1 chaotic attractors in a controllable state space area.…”
Section: Introductionmentioning
confidence: 99%